Feminist Research Methods: Exemplary Readings In The Social Sciences, 1st edition - Nielsen, Joyce McCarl (Routledge, 2020)
Feminist inquiry has affected the nature of research in ail the social and natural sciences over the past decade, but much contemporary writing on feminist methods simply offers a critique of traditional methods. This book, one of the first to offer a practical guide to conducting research informed by feminist methods, is based on the premise that abstract discussion of methodological issues is most meaningful and instructive in conjunction with examples of actual research. A comprehensive and far-reaching introduction defines feminist research and explains how it differs from traditional methodology in the social and natural sciences. In a beautifully clear style, Dr. Nielsen guides the reader through a number of philosophy of science, history of science, and sociology of knowledge issues that are fundamental to understanding the nature of scientific method in its traditional sense and the role of feminist scholarship in the larger intellectual movement that is transforming and redefining scientific methodology. Part One presents the best of feminist commentary on both feminist and traditional methods. Part Two consists of readings that illustrate particular feminist methods, including oral history, linguistic analysis, feminist anthropology informed by feminist literary criticism, and reinterpretation and reanalysis of empirical data from a feminist perspective. Substantive issues addressed in the readings include women's suffrage in the United States, women as shamans, sex differences in suicide rates, sex differences in cognitive abilities, gender dominance through conversation, gender and public policy, and public-private sphere dichotomies.